Mathematical learningmate for children with dyscalculia / Muhammad Amiruddin Azizan and Nor Azlin Rosli - Azizan, Muhammad Amiruddin; Rosli, Nor Azlin (Faculty of Computer and Mathematical Sciences, 2022)
Mathematical Learningmate For Children With Dyscalculia is a research project that aims to assist children with dyscalculia to learn mathematical concepts and arithmetic formulas. Dyscalculia is a type of specific learning disorder that affects people's ability to learn certain math operations like arithmetic data recovery especially children aged 7 years old. Currently, there is a lack of assistive mobile applications for children with dyscalculia and existing applications on the market have poor design choices for dyscalculia children as the bright colors and cluttered layout would confuse them. Mathematical Learningmate For Children With Dyscalculia is carried out with the implementation of the Feature Driven Development (FDD) agile methodology. The Mathematical Learningmate provides the users of the system with several features that are aimed to help assist in learning mathematics. The teachers can upload video-based learning modules to help the children in understanding basic mathematics. The games provided by the system also help in providing the necessary education and provides the teachers a way to measure the current mathematical ability of the children in general. The overall design of the system is also taken into account and are made so that the children can navigate and use the system comfortably.